Síntese, caracterização estrutural e magnética de hexaferritas de bário dopadas com La3+ e Co2+ - Silva, Lucas Marques da (2018)
The barium hexaferrite, an iron oxide of hexagonal geometry, currently plays an important technological role in applications such as permanent magnets, microwave devices and magnetic recording. In this work, we investigated the e ects of doping with La3+ and Co2+ ions on the magnetic and structural properties of barium hexaferrite. Two series of samples were produced, Ba1−αLaαFe12−xCoxO19 with α=0.30, x=(0.0, 0.25, 0.50, 0.75 and 1.0) and α=0.10, x=(0.25 and 0.50). The samples were synthesized by the Ionic Coordination Reaction technical in chitosan polymer matrix and calcined in air 900 ◦C/4 h. The characterization was performed by X ray di ractometry, scanning electron microscopy, vibrating sample magnetometry, Mössbauer spectroscopy and the physical properties measurement system. The X ray di ractograms revealed the presence of the BaFe12O19 type crystalline phase in all samples, with mean particle size ranging from 71 - 58 nm, decreasing with doping. The electron micrographs presented a particle morphology in the form of nanorods, with lengths and diameters around 190 nm and 70 nm, respectively. The analysis detected impurities of α-Fe2O3 and γ-Fe2O3, for the series with α=0.30. The results of the M x H curves showed a dependence of saturation magnetization and coercivity with doping, ranging from 62.9 - 68.8 emu/g, and 5.78 - 2.79 kOe, respectively. A signi- cant improvement (∼10%) at saturation magnetization and an increase in the coercive eld was observed in sample Ba0,9La0,1Fe11,75Co0,25O19. Investigations using Mössbauer spectroscopy demonstrated that the substitution of the Fe3+ by Co2+ ions occurred more strongly in 4f1 and 2a sites of barium hexaferrite. In the M x T measurements, was detected the Hopkinson e ect, an increase in magnetization near the Curie temperature.